2022
DOI: 10.1038/s41598-022-09748-y
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography and magnetic resonance imaging of the brain in experimental human malaria, a prospective cohort study

Abstract: Cerebral malaria is the most serious manifestation of severe falciparum malaria. Sequestration of infected red blood cells and microvascular dysfunction are key contributing processes. Whether these processes occur in early stage disease prior to clinical manifestations is unknown. To help localize and understand these processes during the early stages of infection, we performed 18-F fluorodeoxyglucose positron emission tomography/magnetic resonance imaging in volunteers with Plasmodium falciparum induced bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…After parasite invasion, the RBC undergoes several morphological and rheological alterations, which are manifested by increased RBC membrane rigidity and reduced deformability. [ 15 ] Reorganization of the host RBC eventually culminates in the generation of a novel secretory organelle of parasite origin, the Maurer's clefts, that resides within the host RBC cytoplasm (Figure 2C,D ). During the ring stage of the parasite the Maurer's clefts are single vesicles which move throughout the RBC cytoplasm via Brownian motion.…”
Section: Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…After parasite invasion, the RBC undergoes several morphological and rheological alterations, which are manifested by increased RBC membrane rigidity and reduced deformability. [ 15 ] Reorganization of the host RBC eventually culminates in the generation of a novel secretory organelle of parasite origin, the Maurer's clefts, that resides within the host RBC cytoplasm (Figure 2C,D ). During the ring stage of the parasite the Maurer's clefts are single vesicles which move throughout the RBC cytoplasm via Brownian motion.…”
Section: Malariamentioning
confidence: 99%
“…[76] In fact, there is mounting evidence in CM and experimental cerebral malaria (ECM) that EC junction dysfunction significantly contributes to CM pathogenesis. [24][25][26]79] Positron emission tomography (PET) by Woodford J et al, computerized tomography (CT) scans by Potchen MJ et al, and magnetic resonance imaging (MRI), Seydel et al observed morphological changes at EC-EC junctions in post mortem brains, [9,10,11,[13][14][15] which also exhibit increased sequestration of iRBC and leukocytes in the microvasculature, severe vasculopathy, increased endothelial activation and BBB dysfunction and disruption. In addition, there is persistent upregulation of adhesion molecules (ICAM-1, VCAM-1, E-and P-selectins, and PECAM-1), reduction in tight junction proteins (claudins, occludins, and ZO-1), upregulation of inflammatory cytokines, reduced blood flow, vascular leakage, acute edema of both vasogenic and cytotoxic origin and microhemorrhages, leading to neurological impairment.…”
Section: The Role Of Endothelial Cell-to-cell Adhesionsmentioning
confidence: 99%